The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Tête-à-tête avec la charge mentale | Le Devoir - Saint-Jacques, Sylvie (Le Devoir, 2019)
La fameuse « charge mentale », qui se définit vaguement comme la somme des tâches non rémunérées qui alourdissent le quotidien et la matière grise des femmes, fait l’objet d’un nombre exponentiel d’ouvrages populaires et universitaires ces dernières années. Dans la foulée de Fallait demander de la bédéiste Emma et d’autres variations sur le même thème, Si nous sommes égaux, je suis la fée des dents est le fruit du travail de recherche pratique et de réflexions de la travailleuse sociale Amélie Châteauneuf, qui a voulu concevoir un outil pour les couples avec ou sans enfant.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; charge mentale; conciliation famille-travail; division sexuelle du travail; famille; maternité; projet charge mentale; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; thématiques; travail

L’environnement, un nouvel enjeu de charge mentale ? Et si les femmes devaient ajouter à leur liste de tâches… la sauvegarde de la planète! - Souissi, Takwa (Gazette des femmes, 2019)
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; charge mentale verte; environnement; inégalités; projet charge mentale; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; santé; systèmes d'oppressions; thématiques